Monitoring cellular uptake and cytotoxicity of copper(II) complex using a fluorescent anthracene thiosemicarbazone ligand - Kate, Anup N.; Kumbhar, Anupa A.; Khan, Ayesha A.; Joshi, Pranaya V.; Puranik, Vedavati G. (Bioconjugate Chemistry, 2014)
The thiosemicarbazone derivative of anthracene (ATSC, anthracene thiosemicarbazone I) and its copper(II) complex (CuATSC, 2) were synthesized and characterized by spectroscopic, electrochemical, and crystallographic techniques. Interaction of 1 and 2 with calf thymus (CT) DNA was explored using absorption and emission spectral methods, and viscosity measurements reveal a partial-intercalation binding mode. Their protein binding ability was monitored by the quenching of tryptophan emission using bovine serum albumin (BSA) as a model protein. Furthermore, their cellular uptake, in vitro cytotoxicity testing on the HeLa cell line, and flow cytometric analysis were carried out to ascertain the mode of cell death. Cell cycle analysis indicated that 1 and 2 cause cell cycle arrest in sub-G1 phase.

Synthesis, DNA interaction and anticancer activity of 2-anthryl substituted benzimidazole derivatives - Sontakke, Vyankat A.; Kate, Anup N.; Ghosh, Sougata; More, Piyush; Gonnade, Rajesh G.; Kumbhar, Navanath M.; Kumbhar, Anupa A.; Chopade, Balu Ananda; Shinde, Vaishali S. (New Journal of Chemistry, 2015)
2-Anthryl benzimidazole derivatives (5-7) with hydrogen, carboxyl and benzoyl substituents at the 5th position have been synthesized using a silica supported periodic acid catalyst. The DNA cleavage activity of 5-7 was studied in the presence of light using pBR322 plasmid DNA and was shown to vary with substitution at the 5th position of benzimidazole derivatives. DNA binding studies using ethidium bromide displacement assay demonstrated the non-intercalative binding mode of 5-7. The anticancer activity of these target molecules was tested against MCF-7 and HL-60 cell lines, and they exhibited remarkable activity in the micromolar range. Cellular uptake and morphological changes were confirmed by fluorescence and confocal microscopy. A molecular docking study was carried out to explore the DNA binding mechanism of 5-7.